EFFECT OF COMPUTER ASSISTED INSTRUCTION ON THE RETENTION ABILITY OF TECHNICAL COLLEGE STUDENTS IN ELECTRICAL INSTALLATION AND MAINTENANCE WORK IN ENUGU STATE (NAU Journal of Technology and Vocational Education, 2024)
This study investigated effect of Computer Assisted Instruction on the retentionability of technical college students in Electrical Installation and MaintenanceWork in Enugu State. A research question and a null hypothesis guided the study.Quasi experimental research design was adopted for the study. The sample usedfor the study consisted of 22 NTC II students made up of 14 males and 8 females.Purposive sampling technique was used to select two schools from Udi and Enugueducation zones. An intact class was used in each of the schools which were taggedexperimental and control group respectively. The instrument used for datacollection was a 50 objective questions developed by the researcher which wasadministered as pre-test, post-test and delayed post-test to the experimental andcontrol groups respectively. Pearson correlation coefficient formula was used toestablish the reliability of the instrument which yielded 0.81 coefficient reliability.The research question was answered using mean scores whereas the hypothesiswas analyzed using ANCOVA. The mean scores and ANCOVA were calculatedusing SPSS version 20. The findings showed that CAI significantly increased thestudents’ retention ability. In view of the finding, it was recommended amongothers that CAI should be formally adopted in technical colleges, secondary andvocational schools for instruction in Electrical Installation and Maintenance Workto improve retention ability of students.
Keywords: Computer assisted instruction, Retention ability, Electrical Installation and Maintenance Work.